2008
DOI: 10.1525/jer.2008.3.4.57
|View full text |Cite
|
Sign up to set email alerts
|

Survey of U.S. Human Research Protection Organizations: Workload and Membership

Abstract: In a national survey of institutions with federally assured human research protection programs, we obtained workload and other relevant data on their Institutional Review Boards (IRBs) and management organizations. The number of IRBs increased substantially from 1995 to 2005/06 (491 to 2,728 IRBs) with a further increase in 2008 to 3,853 IRBs. Nationally, IRBs reviewed over a quarter million research applications in the year prior to our survey, of which 35% were new applications requiring full committee revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 8 publications
2
33
0
Order By: Relevance
“…The current report extends prior research reported in the accompanying article (Catania et al, 2008) on workload and institutional review board (IRB) composition to consider IRBs that review (MHRAs). Mental health–related research may place added demands on the IRB system.…”
supporting
confidence: 59%
“…The current report extends prior research reported in the accompanying article (Catania et al, 2008) on workload and institutional review board (IRB) composition to consider IRBs that review (MHRAs). Mental health–related research may place added demands on the IRB system.…”
supporting
confidence: 59%
“…Institutions have a responsibility to provide facilities and staff. In Catania et al [8] study, in the US, heavy workload per IRB member was commented on but not the number of administrators.…”
Section: Discussionmentioning
confidence: 99%
“…Catania et al [8] reported on a 2004 national survey in the US of Institutional Review Boards (IRB). They remarked on ' …the need for research to (a) examine workload and its effects on review quality, research costs, and faculty morale .…”
Section: Discussionmentioning
confidence: 99%
“…The sheer amount of research now being conducted has resulted in an unprecedented increase in workload and placed a severe burden on Institutional Review Boards (IRBs 1 ) [2]. In addition, in recent years there has been a growing trend towards multisite clinical research, complicating the effectiveness of an institutionally-based oversight system [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Catania et al showed that the number of U.S. IRBs increased by 41% from 2004 to 2008 [2]. According to the March 2013 data from the Office for Human Research Protections (OHRP), there are 2,937 actively registered U.S. IRB organizations (IORGs) and 1,983 non-U.S. IORGs, which include 3,589 individual U.S. IRBs and 2,252 non-U.S. IRBs, respectively [7].…”
Section: Introductionmentioning
confidence: 99%